2022
DOI: 10.5194/essd-14-3137-2022
|View full text |Cite
|
Sign up to set email alerts
|

STAR NDSI collection: a cloud-free MODIS NDSI dataset (2001–2020) for China

Abstract: Abstract. Snow dynamics are crucial in ecosystems, affecting radiation balance, hydrological cycles, biodiversity, and human activities. Snow areas with notably diverse characteristics are extensively distributed in China, mainly including Northern Xinjiang (NX), Northeast China (NC), and the Qinghai–Tibet Plateau (QTP). Spatiotemporal continuous snow monitoring is indispensable for ecosystem maintenance. Nevertheless, the formidable challenge of cloud obscuration severely impedes data collection. In the past … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…The global cloud-gap-filled MODIS NDSI dataset (MOD10A1F) were generated by retaining clear-sky views of the surface from previous days in MOD10A1 NDSI product to fill the cloud-covered pixel [81,82]. However, this product performs poorly in China, where periodic and transient snow is dominant [59], and so does HMA. Jing et al [59] developed the Spatio-Temporal Adaptive fusion method with erroR correction to generate the cloud-free STAR NDSI collection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The global cloud-gap-filled MODIS NDSI dataset (MOD10A1F) were generated by retaining clear-sky views of the surface from previous days in MOD10A1 NDSI product to fill the cloud-covered pixel [81,82]. However, this product performs poorly in China, where periodic and transient snow is dominant [59], and so does HMA. Jing et al [59] developed the Spatio-Temporal Adaptive fusion method with erroR correction to generate the cloud-free STAR NDSI collection.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, since the NDSI from C6 is a more accurate description index of the snow detection as compared to the FSC from C5 [56], more studies are shifting to the use of MODIS C6 products. Research works have demonstrated that the MODIS snow cover product C6 has high accuracy in the Tibetan Plateau, with Terra product C6 being comparable to Terra product C5, and Aqua product C6 truly having better accuracy than Aqua product C5 [57][58][59]. However, the data gaps from cloud contamination in C6 still exist, and thus a cloud removal algorithm for MODIS NDSI products is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…The actual date of snow melt was identified on a pixelwise, per‐annum basis as the first three consecutive days with NDSI below 0.35, corresponding to 35% snow cover averaged across the pixel. This threshold was determined by a sensitivity analysis; including thresholds of 10%, 15%, 35%, and 50%, based on the thresholds of 50% and 10% as used by O'Leary et al (2018) and Jing et al (2022), respectively. We concluded that 35% gave snow melt dates that aligned with those of O'Leary et al (2018) and of ERA‐5 Land snow cover data, whereas lower thresholds were unduly late, likely influenced by surface water, and higher thresholds were characterized by a high degree of noise and erroneous mid‐winter snow melt.…”
Section: Methodsmentioning
confidence: 99%
“…However, this product has data gaps caused by cloud cover. Shen et al utilized the spatio-temporal adaptive fusion method with error correction (STAR) to fill the data gaps, and obtained a daily stretched seamless NDSI product for China with 500 m spatial resolution [37]. Still, for the TP, which is characterized by complex topography and strong spatial heterogeneity snow cover, it is difficult to obtain detailed and accurate snow cover distribution or change information from such data, so the spatial and temporal resolution of optical remote sensing data is highly demanded.…”
Section: Introductionmentioning
confidence: 99%